Cystic meningiomas: MR characteristics and surgical correlations. - Wasenko, J J; Hochhauser, L; Stopa, E G; Winfield, J A (American Journal of Neuroradiology, 1994)
PURPOSE To describe the MR appearance of cystic meningiomas, and to correlate the MR appearance with the surgical and neuropathologic findings. METHODS Eight patients with cysts associated with meningiomas were studied on a 1.5-T MR system. Unenhanced sagittal T1- and axial T2-weighted images were obtained in all patients. Axial and coronal gadopentetate dimeglumine-enhanced T1-weighted spin-echo images were obtained in seven patients. Additional sagittal T1-weighted spin-echo contrast-enhanced images were obtained in four patients. RESULTS The cystic components were intratumoral and eccentric in two cases, intraparenchymal in one case, and extraparenchymal (trapped cerebrospinal fluid) in five cases. Cyst wall enhancement was present in two of seven cases performed with intravenous gadopentetate dimeglumine. There was no correlation between cyst signal intensity and cyst content. A preoperative diagnosis of cystic meningioma was possible in all eight cases. CONCLUSIONS MR demonstrates the extradural location of the tumor and its cystic component, correlates well with the surgical presentation and the neuropathologic results, and allows the preoperative diagnosis of cystic meningioma based on the MR findings. Division into three types of cysts aids the neurosurgeon, who must decide whether total resection is feasible. To obtain total resection and reduce the risk of recurrence with an intratumoral cyst, the surgeon must ensure that the plane of resection is in fact between the thin enhancing membrane of the tumor cyst and the adjacent arachnoid. In cases in which the cyst is trapped cerebrospinal fluid or intraparenchymal in location, the cyst wall adjacent to or within the brain parenchyma is not included in the resection.